Inhibition of SLC drug transporter activities by environmental bisphenols. (April 2017) - Bruyere, Arnaud; Hubert, Céline; Le Vee, Marc; Chedik, Lisa; Sayyed, Katia; Stieger, Bruno; Denizot, Claire; Parmentier, Yannick; Fardel, Olivier
Abstract: The plastic component bisphenol A (BPA) is suspected to exert deleterious effects towards human health and targets various cellular and molecular pathways, including activity of ATP-binding cassette drug transporters. The present study was designed to determine whether BPA and some derivatives, like its substitutes bisphenol F (BPF) and bisphenol S (BPS) and the flame retardant tetrabromobisphenol A (TBBPA), may additionally interact with solute carrier (SLC) drug transporters. Activities of the various following SLC transporters were inhibited in a major way (by > 60%) by 100 μM bisphenols: OCT1 and MATE1 (by BPA and TBBPA), OATP1B1 (by BPA, BPF and TBBPA), OATP1B3 and NTCP (by TBBPA) and OAT3 (by BPA, BPF, BPS and TBBPA); by contrast, activities of other transporters were not impacted (MATE2-K) or were stimulated (notably OCT1 by BPS and OCT2 by BPF). Transporter inhibitions due to bisphenols were concentrations-dependent, with half maximal inhibitory concentrations (IC50 ) ranging from 0.5 μM to 73.5 μM. BPA was finally shown to be not transported by OAT3, although inhibiting this transporter in a competitive manner. Taken together, these data indicate that bisphenols interact with SLC transporters, at concentration levels however rather higher than those occurring in humans in response to environmental exposure. Highlights: Environmental bisphenols inhibited activities of various SLC drug transporters. OCT1, MATE1 and OATP1B1 were thus notably targeted by bisphenol A. Bisphenol A also competitively inhibited OAT3, without however being transported. High concentrations of bisphenols were however needed for SLC transporter inhibitions.